This town two parties and a funeral--plus, plenty of valet parking!--in America's gilded capital - Leibovich, Mark (New York Blue Rider Press, 2013)
"A book about contemporary political culture in Washington, DC"--
Includes bibliographical references
1
Keywords: POLITICAL SCIENCE / Government / National; POLITICAL SCIENCE / Political Process / General; Political culture -- Washington (D.C.); Politicians -- United States; United States -- Politics and government